Human Capital, HRM Practices and Organizational Performance in Pakistani Construction Organizations: The Mediating Role of Innovation - Sarwar, Huma; Khan, Bilal; Nadeem, Kashif; Aftab, Junaid (Archives of Business Research, 2016)
Human capital and human resource management practices play a vital role in success of any organization. When employees feel satisfy with human resource policies of an organization they give their best to increase the organizational performance. Construction industry provides job opportunities to large number of people in all over the world.In Pakistan, construction industry is making progress with rapid rate. To investigate the importance of human resources in organizational performance, a research was carried out to check the influence of human capital and human resource management practices on organizational performance with the mediating role of innovation in construction industry of Pakistan. The data for this study was collected from the 315 employees from construction companies of Pakistan through structured questionnaires using simple random sampling. Data analysis technique like structural equation modeling was applied using SPSS AMOS. The findings indicated that human capital and human resource management practices are positively associated with organizational performance. Also, innovation mediates the relationship between independent variables (human capital & HRM practices) and organizational performance in construction industry of Pakistan.